Cyclic AMP response element-binding protein (CREB) transcription factor in astrocytic synaptic communication - Kim, Jooyoung; Kaang, Bong-Kiun (Frontiers in Synaptic Neuroscience, 2023)
Astrocytes are known to actively participate in synaptic communication by forming structures called tripartite synapses. These synapses consist of presynaptic axon terminals, postsynaptic dendritic spines, and astrocytic processes where astrocytes release and receive transmitters. Although the transcription factor cyclic AMP response element (CRE)-binding protein (CREB) has been actively studied as an important factor for mediating synaptic activity-induced responses in neurons, its role in astrocytes is relatively unknown. Synaptic signals are known to activate various downstream pathways in astrocytes, which can activate the CREB transcription factor. Therefore, there is a need to summarize studies on astrocytic intracellular pathways that are induced by synaptic communication resulting in activation of the CREB pathway. In this review, we discuss the various neurotransmitter receptors and intracellular pathways that can induce CREB activation and CREB-induced gene regulation in astrocytes.